Quality Assurance and Accreditation in MBA Programs: A Systematic Review of Emerging Trends and Frameworks - Norman, Efrita; Paramansyah, Arman; Feviasari, Heni; Pahlawati, Enah (Al-Qalam Institue, 2025)
Accreditation and quality assurance (QA) are crucial for the development and global competitiveness of MBA programs. This study systematically reviews trends, frameworks, and stakeholder perspectives on accreditation in MBA education. It aims to identify common QA practices, explore stakeholder roles, and examine how accreditation affects institutional performance and strategic priorities. The study analyzed 48 empirical and conceptual studies from Scopus-indexed sources using thematic analysis, focusing on five key areas: definitions and theories of quality, comparative accreditation models, stakeholder involvement in QA, challenges in autonomous institutions, and the impact of accreditation on performance indicators. Findings show that accreditation fosters both standardization and innovation, particularly in autonomous and non-Western institutions. Stakeholder perceptions significantly influence QA success, with collaboration and transparency enhancing legitimacy. Empirical evidence highlights a strong correlation between accreditation and improvements in graduate employability, student satisfaction, institutional governance, and market positioning. This review contributes to the discourse on business education quality, identifying gaps and recommending more inclusive and adaptive accreditation strategies for institutions, accrediting bodies, and policymakers to enhance educational outcomes and global relevance.